Human-to-Cattle Mycobacterium tuberculosis Complex Transmission in the United States - Lombard, Jason E.; Patton, Elisabeth A.; Gibbons-Burgener, Suzanne N.; Klos, Rachel F.; Tans-Kersten, Julie L.; Carlson, Beth W.; Keller, Susan J.; Pritschet, Delora J.; Rollo, Susan; Dutcher, Tracey V.; Young, Cris A.; Hench, William C.; et al. (Frontiers in Veterinary Science, 2021)
The Mycobacterium tuberculosis complex (MTBC) species includes both M. tuberculosis, the primary cause of human tuberculosis (TB), and M. bovis, the primary cause of bovine tuberculosis (bTB), as well as other closely related Mycobacterium species. Zoonotic transmission of M. bovis from cattle to humans was recognized more than a century ago, but transmission of MTBC species from humans to cattle is less often recognized. Within the last decade, multiple published reports from around the world describe human-to-cattle transmission of MTBC. Three probable cases of human-to-cattle MTBC transmission have occurred in the United States since 2013. In the first case, detection of active TB disease (M. bovis) in a dairy employee in North Dakota prompted testing and ultimate detection of bTB infection in the dairy herd. Whole genome sequencing (WGS) demonstrated a match between the bTB strain in the employee and an infected cow. North Dakota animal and public health officials concluded that the employee’s infection was the most likely source of disease introduction in the dairy. The second case involved a Wisconsin dairy herd with an employee diagnosed with TB disease in 2015. Subsequently, the herd was tested twice with no disease detected. Three years later, a cow originating from this herd was detected with bTB at slaughter. The strain in the slaughter case matched that of the past employee based on WGS. The third case was a 4-month-old heifer calf born in New Mexico and transported to Texas. The calf was TB tested per Texas entry requirements and found to have M. tuberculosis. Humans are the suspected source of M. tuberculosis in cattle; however, public health authorities were not able to identify an infected human associated with the cattle operation. These 3 cases provide strong evidence of human-to-cattle transmission of MTBC organisms and highlight human infection as a potential source of introduction of MTBC into dairy herds in the United States. To better understand and address the issue, a multisectoral One Health approach is needed, where industry, public health, and animal health work together to better understand the epidemiology and identify preventive measures to protect human and animal health.